Correlation of polymer wear-debris generation between microscratching and macroscopic wear. (January 2016) - Liu, Yanyan; Song, Shaoxian; Timmers, Heiko
Abstract: The paper investigates the effect of the tip attack-geometry on wear-debris generation of polymers. Microscratching and pin-on-disk macroscopic wear experiments are carried out to establish the correlation between microscratching and macroscopic wear. Results show that no debris found on PET using a conical tip. However, debris were observed on PET using a cubic corner tip. Furthermore, the specific wear rates of tested polymers agree well with Ratner–Lancaster correlation. However, correlation of the wear rate between microscratching and macroscopic wear shows a reverse relationship which suggests that wear mechanisms of polymers between microtribology and macroscopic wear may exist. Highlights: Investigating the effects of the tip attack-geometry on wear-debris generation. Correlation of the wear rate of microscratching and pin-on-disk macroscopic wear. Debris on PET was found by the cubic corner tip, not the conical tip. Hardness of polymers measured here is consistent with other publications. A reverse relationship of the wear rate between micro-and macro scale was obtained.